Cancer stem cells in colorectal cancer: a review. Issue 2 (23rd September 2017) - Munro, Matthew J; Wickremesekera, Susrutha K; Peng, Lifeng; Tan, Swee T; Itinteang, Tinte
Abstract : Colorectal cancer (CRC) is the second most common cancer in women and the third most common in men. Adenocarcinoma accounts for 90% of CRC cases. There has been accumulating evidence in support of the cancer stem cell (CSC) concept of cancer which proposes that CSCs are central in the initiation of cancer. CSCs have been the focus of study in a range of cancers, including CRC. This has led to the identification and understanding of genes involved in the induction and maintenance of pluripotency of stem cells, and markers for CSCs, including those investigated specifically in CRC. Knowledge of the expression pattern of CSCs in CRC has been increasing in recent years, revealing a heterogeneous population of cells within CRC ranging from pluripotent to differentiated cells, with overlapping and sometimes unique combinations of markers. This review summarises current literature on the understanding of CSCs in CRC, including evidence of the presence of CSC subpopulations, and the stem cell markers currently used to identify and localise these CSC subpopulations. Future research into this field may lead to improved methods for early detection of CRC, novel therapy and monitoring of treatment for CRC and other cancer types.